Coupling of BGK lattice Boltzmann method and experimental rheological/thermal behavior of Al2O3–oil nanolubricant for modeling of a finned thermal storage. Issue 8 (11th January 2022) - Aqeel Ashraf, Muhammad; Liu, Zhenling; Hasani Malekshah, Emad; Kolsi, Lioua; Kadhim Hussein, Ahmed
Abstract : Purpose: The purpose of the present work is to investigate the hydrodynamic and thermal performance of a thermal storage based on the numerical and experimental approaches using the lattice Boltzmann method and the experimental observation on the thermo-physical properties of the operating fluid. Design/methodology/approach: For this purpose, the Al2 O3 nanoparticle is added to the lubricant with four nanoparticle concentrations, including 0.1, 0.2, 0.4 and 0.6Vol.%. After preparing the nanolubricant samples, the thermal conductivity and dynamic viscosity of nanolubricant are measured using thermal analyzer and viscometer, respectively. Finally, the extracted data are used in the numerical simulation using provided correlations. In the numerical process, the lattice Boltzmann equations based on Bhatnagar–Gross Krook model are used. Also, some modifications are applied to treat with the complex boundary conditions. In addition, the second law analysis is used based on the local and total views. Findings: Different types of results are reported, including the flow structure, temperature distribution, contours of local entropy generation, value of average Nusselt number, value of entropy generation and value of Bejan number. Originality/value: The originality of this work is combining a modern numerical methodology with experimental data to simulate the convective flow for an industrial application.